PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. KALIMIAS BINTANG PRATAMA CABANG LOMBOK TENGAH - Khaerul Hadi; Baiq Nurul Hidayah (Sekolah Tinggi Ilmu Ekonomi AMM, 2019)
The purpose of this research is to investigate the influence of workload variable, work environment and compensation toward employee performance, and to knows the variable that has dominant effects on employee performance in PT. Kalimias Bintang Pratama Branch of Central Lombok. The population in this research is employees in PT. Kalimias Bintang Pratama Branch of Central Lombok. The number of samples that taken was 30 peoples. Data collection techniques using questionnaires, and data analysis using multiple linear regression analysis. The results of multiple linear regression analysis show that simultaneously of the three indicators of independent variables significantly have effects of employees performance in PT. Kalimias Bintang Pratama Branch of Central Lombok. In accordance with partial, the workload, work environment and compensation have positive and significant effects on the performance of employees at PT. Kalimias Bintang Pratama Branch of Central Lombok